Шляхи удосконалення функціонування МВС України в умовах проведення реформ - Глуховеря, В. А.; Глуховеря, В. А.; Gluhoverya, V. A. (Одеса : Видавничий дім "Гельветика", 2016)
У статті висвітлюються напрями подальшого розвитку МВС України, з'ясування головних складників, що потребують реалізації в умовах проведення реформ. Аналізуються заходи, висвітлені в Концепції першочергових заходів реформування системи Міністерства внутрішніх справ та Стратегії розвитку органів внутрішніх справ України, та пропонуються шляхи їх подальшої реалізації.

Пути усовершенствования функционирования МВД Украины в условиях проведения реформ. В статье исследуются особенности финансово-экономического обеспечения политики МВД Украины в правоохранительной сфере, освещаются проблемные вопросы в сфере финансирования МВД Украины и предлагаются пути их решения.

Ways of the functioning improving of the Ministry of internal affairs of Ukraine in reforms conditions. Directions of further development of МВС of Ukraine, finding out of main constituents that need realization in the conditions of realization of reforms are illuminated in the article. Measures are analyzed lighted up in Conception of near-term measures of reformation of the system of Ministry of internal affairs and Strategy of development of organs of internal affairs of Ukraine and ways are offered them further realization. European integration of Ukraine obligates our state to provide the effective functioning of institutes, that will guarantee supremacy of right, inhibition of rights and freedoms of man and citizen, them effective defense. One of such tasks there is formation of Ministry of internal affairs as a civil organ of the European standard. For that time that passed with the acceptance of Strategy already separate questions in relation to reformation of organs of internal affairs were decided.: the National police, National household troops, is created, liquidations of subdivisions of a transport militia with the transmission of their functions to the territorial organs of the National police; the special subdivisions are liquidated on a fight against the organized crime; a veterinary militia that duplicated the functions of veterinary and phytosanitary services is liquidated; the State motor-car inspection is liquidated; status of militia is revised in matters of children in accordance with the requirements of international law in the field of a juvenal justice; the structure of Ministry of internal affairs of Ukraine is changed, the re-attestation of workers is conducted et al. Today the basic problem of the system of the organizationally-administrative providing of realization of public policy of Ministry of internal affairs of Ukraine in a law-enforcement sphere is the insufficient skilled providing of process of realization of public policy, an only coordinating organ that would engage in the decision of strategic tasks of public policy and coordinated activity of all subjects is absent. Today the organizationally-administrative mechanism of realization of public policy of Ministry of internal affairs of Ukraine in a law-enforcement sphere has an non effective horizontal model of co-ordination of this politics, the system of organs and institutes, that forms and will realize this politics, is ineffective.
Глуховеря В. А. Шляхи удосконалення функціонування МВС України в умовах проведення реформ / В. А. Глуховеря // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: В. В. Завальнюк (голов. ред.) [та ін.] ; відп. за вип. М. В. Афанасьєва. – Одеса : Видавничий дім "Гельветика", 2016. – Вип. 77. – С. 70-74.
Keywords: концепція; стратегія; правоохоронна сфера; правоохоронні органи; МВС України; реформування; політика; державна політика; концепция; стратегия; политика; государственная политика; правоохранительная сфера; правоохранительные органы; МВД Украины; реформирование; public policy; conception; strategy; law-enforcement sphere; law enforcement authorities; Ministry of internal affairs of Ukraine; reformation